Islam dan Hak Asasi Manusia dalam Konsepsi Fathi Osman - Muafiah, Evi (Program Pascasarjana UIN Sunan Ampel Surabaya, 2011)
The relation of Islam as a religion and the notion of human right has attracted a lot of attention both from the activists and the academics. One of the academics that has paid a good deal of attention to this issue is an Egyptian scholar named Fathi Osman. This paper is dedicated to explore his ideas, suggestions and conceptions on the issue at hand. It contends that Osman is mainly concerned with the synthesis of Islamic concept and the notion of human right adopted by the international community. The paper exposes Osmanâs strategies in pursuing the synthesis, which begins by careful investigation on both Islamic and modern concepts of human right, then followed by identifying the strength and weakness of each concept. This strategy is aimed at gaining a clear idea about how a new concept of human right should be formulated. The paper will also ask whether Osmanâs synthesis is both practical and conceptual. By practical, we mean a concept which rooted in the real experiences as far as human rights are concerned. And by conceptual, we mean whether Osmanâs ideas are derived from the theoretical analysis of both Islamic sources and the sources of modern idea on human rights.